A GntR Family Transcription Factor in Streptococcus mutans Regulates Biofilm Formation and Expression of Multiple Sugar Transporter Genes - Li, Zongbo; Xiang, Zhenting; Zeng, Jumei; Li, Yuqing; Li, Jiyao (Frontiers in Microbiology, 2019)
GntR family transcription factors have been implicated in the regulation of carbohydrate transport and metabolism in many bacteria. However, the function of this transcription factor family is poorly studied in Streptococcus mutans, which is a commensal bacterium in the human oral cavity and a well-known cariogenic pathogen. One of the most important virulence traits of S. mutans is its ability to transport and metabolize carbohydrates. In this study, we identified a GntR transcription factor in S. mutans named StsR (Sugar Transporter Systems Regulator). The deletion of the stsR gene in S. mutans caused a decrease in both the formation of biofilm and the production of extracellular polysaccharides at early stage. Global gene expression profiling revealed that the expression levels of 188 genes were changed in the stsR mutant, which could be clustered with the sugar PTS and ABC transporters. Furthermore, StsR protein was purified and its conserved DNA binding motif was determined using electrophoretic mobility shift assays (EMSA) and DNase I footprinting assays. Collectively, the results of this research indicate that StsR is an important transcription factor in S. mutans that regulates the expression of sugar transporter genes, production of extracellular polysaccharides and formation of biofilm.